STUDENTS’ MATHEMATICS LEARNING ACTIVITIES IN CLASS X.4 SMAN 2 DUMAI ON COOPERATIVE LEARNING TYPE TEAM GAMES TOURNAMENT - Arni Iswari (Jurnal Prinsip Pendidikan Matematika, 2020)
The student involvement of class X.4 of SMAN 2 Dumai in the learning mathematics is very low. Students rarely want to be involved and actively participate in efforts to develop their knowledge and skills. Learning activities are still centered on the teacher (teacher’s centered) because the teacher is still dominant using the lecture method so that the teacher is more active than the student which causes the learning process to become rigid, less support the development of students' attitudes, knowledge, and skills. The low students’mathematics learning activities are also caused by the low level of student understanding of the subject matter concept. Therefore, this study aims to improve students' mathematics learning activities through the implementation of Cooperative Learning type Team Games Tournament (TGT). This study was a classroom action research consisting of two cycles. Data collection is done by filling out the observation sheets conducted by peers during the learning process. Based on the results of data analysis it can be concluded that the students’ mathematics learning activities in class X.4 of SMAN 2 Dumai have increased from an average of 76.46% (good) in the first cycle to 94.14% (very good) in the second cycle.